Disinformasi Digital dan Integritas Pemilu di Wilayah Perbatasan: Studi Kasus Pemilihan Lokal di Merauke - Katayu, Damianus (Indo Publishing, 2025)
This study aims to explore the dynamics of digital disinformation at each stage of the local elections in Merauke and analyze its implications for the integrity of the democratic process in the border region. A qualitative approach with an exploratory case study strategy was used to deeply understand the phenomenon of disinformation in a complex geographic, social, and political context. Data were collected through in-depth interviews, focus group discussions (FGDs), document studies, and online observations on social media platforms such as Facebook and WhatsApp. The analysis was carried out thematically with triangulation of data sources to ensure the validity of the findings. The results of the study show that digital disinformation in Merauke has distinctive characteristics in the form of narratives based on ethnicity, religion, and border issues. Disinformation is spread through local community networks and social media, with the main actors being political sympathizers, campaign teams, and anonymous accounts across regions. This disinformation has a real impact on the integrity of the election, including triggering political polarization, increasing reports of violations, and hampering the campaign process and logistics distribution. This study contributes to the literature on election disinformation in border regions and recommends strengthening digital literacy, the role of local figures, and collaboration between institutions to mitigate disinformation. Further studies are recommended to develop community-based intervention models with adaptive technology support.